Answer:
65.21739130434783
Step-by-step explanation:
3(24) + 2(24) + 5.39(24) = 72 + 48 + 129.36 = 249.36 ~ 249m^2
<span>Total Surface Area: </span>
<span>(add to the above) </span>
<span>2(1/2)(3)(2) = 6m^2 (area of the two triangles) </span>
<span>6 + 149 = 155m^2 </span>
X is 45, z is 45, and y is 90
No because root(3)(x+8+1) is equal to x^3 -9 and (x-1)^3+8 is equal to root (3)(√x−8−1)
<u>Given</u><u> </u><u>:</u>
<u>To</u><u> </u><u>Find</u><u> </u><u>:</u>
<u>Answer</u><u> </u><u>:</u>
- x + y = 4 ....[Equation (i)]
- x + y = 1......[Equation (ii)]
<u>Adding</u><u> </u><u>eqⁿ (ii) </u><u>and</u><u> eqⁿ (i) we get :</u>
→ x + y + x - y = 4 + 1
→ 2x = 5
→ x = 5/2
→ x = 2.5
<u>Now</u><u>,</u><u> </u><u>put</u><u> </u><u>the</u><u> </u><u>value </u><u>of</u><u> </u><u>x</u><u> </u><u>=</u><u> </u><u>5</u><u>/</u><u>2</u><u> </u><u>in</u><u> </u><u>eqⁿ</u><u> </u><u>(</u><u>i</u><u>)</u><u> </u><u>we</u><u> </u><u>get</u><u> </u><u>:</u>
→ x + y = 4
→ 5/2 + y = 4
→ y = 4 - 5/2
→ y = 1.5